2021
DOI: 10.1097/yct.0000000000000769
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Sham-Controlled Study of Transcranial Direct Current Stimulation as an Augmentation Intervention for the Attenuation of Motor Deficits in Patients With Stroke

Abstract: Introduction: Most studies of transcranial direct current stimulation (tDCS) for motor deficits in patients with stroke administered few sessions of tDCS and with low current amplitude.Methods: During 2015 to 2019, we randomized 60 inpatients with ischemic/hemorrhagic stroke and motor deficits to true or sham tDCS. Transcranial direct current stimulation was administered at 2-to 3-mA current strength, twice daily, 6 days a week, for 2 weeks; anode and cathode were placed over ipsilesional and contralesional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The number of participant assessed with the BI, the upper extremity FMA, the lower extremity FMA, and the MAS tested was 515, 913, 179, and 172, respectively. Despite all the studies being randomized controlled trials, out of the 31 studies that were included in this review, one study reported significant differences between the tDCS and sham groups at baseline (Pinto et al, 2021) and some studies made no mention of baseline differences either in their discussion or with a statistical analysis (Allman et al, 2016;Achacheluee et al, 2018;Oveisgharan et al, 2018). The rest of the included studies reported that the sham and tDCS groups were similar at baseline.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The number of participant assessed with the BI, the upper extremity FMA, the lower extremity FMA, and the MAS tested was 515, 913, 179, and 172, respectively. Despite all the studies being randomized controlled trials, out of the 31 studies that were included in this review, one study reported significant differences between the tDCS and sham groups at baseline (Pinto et al, 2021) and some studies made no mention of baseline differences either in their discussion or with a statistical analysis (Allman et al, 2016;Achacheluee et al, 2018;Oveisgharan et al, 2018). The rest of the included studies reported that the sham and tDCS groups were similar at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…Some manuscripts reported more than one assessment. Ten of them investigated the BI (Kim et al, 2010;Hesse et al, 2011;Khedr et al, 2013;Fusco et al, 2014;Yi et al, 2016;Koo et al, 2018;Bolognini et al, 2020;Bornheim et al, 2020;Yao et al, 2020;Pinto et al, 2021), 25 included the upper extremity FMA (Lindenberg et al, 2010;Bolognini et al, 2011Bolognini et al, , 2020Hesse et al, 2011;Nair et al, 2011;Khedr et al, 2013;Rossi et al, 2013; FIGURE 1 | Effects of transcranial direct current stimulation (tDCS) on stroke recovery as assessed by the post-intervention data of the tDCS and sham groups for the Barthel Index. Fusco et al, 2014;Viana et al, 2014;Ang et al, 2015;Triccas et al, 2015;Allman et al, 2016;Kim et al, 2016;Rocha et al, 2016;Straudi et al, 2016;Yi et al, 2016;Mazzoleni et al, 2017;Achacheluee et al, 2018;Oveisgharan et al, 2018;Beaulieu et al, 2019;Edwards et al, 2019;Jin et al, 2019;Alisar et al, 2020;Bornheim et al, 2020;Liao et al, 2020;Yao et al, 2020;Pinto et al, 2021;Prathum et al, 2021), five included the lower extremity FMA (Chang...…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is so far conflicting evidence from systematic reviews of randomized controlled trials (RCTs) on the effectiveness of different NIBS approaches for improving different domains of cognitive function after stroke. New RCTs on TMS and tDCS 13,24,35,36,37 were not included in the prior meta-analysis. To acquire integrated results, it is required to expand these investigations.…”
Section: Introductionmentioning
confidence: 99%